2017
DOI: 10.1073/pnas.1704925114
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the effects of selection and loss bias on gene dynamics

Abstract: We combine mathematical modeling of genome evolution with comparative analysis of prokaryotic genomes to estimate the relative contributions of selection and intrinsic loss bias to the evolution of different functional classes of genes and mobile genetic elements (MGE). An exact solution for the dynamics of gene family size was obtained under a linear duplication-transfer-loss model with selection. With the exception of genes involved in information processing, particularly translation, which are maintained by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 86 publications
2
26
0
Order By: Relevance
“…To overcome this limitation, we used a phylogenomic reconstruction tool (COUNT) [46] that infers the distribution of gene gains and losses along the branches of a phylogenetic tree to obtain maximum likelihood estimates of the duplication, HGT, and loss rates under the assumption of neutrality [44,45]. Given such "neutral-equivalent" estimates, it is possible to recover the selection coefficient provided that the real value of at least one parameter is known.…”
Section: -P3mentioning
confidence: 99%
See 3 more Smart Citations
“…To overcome this limitation, we used a phylogenomic reconstruction tool (COUNT) [46] that infers the distribution of gene gains and losses along the branches of a phylogenetic tree to obtain maximum likelihood estimates of the duplication, HGT, and loss rates under the assumption of neutrality [44,45]. Given such "neutral-equivalent" estimates, it is possible to recover the selection coefficient provided that the real value of at least one parameter is known.…”
Section: -P3mentioning
confidence: 99%
“…-The interdependence between the cost of 58001-p5 Box plots were generated by pooling multiple gene families from the same class of parasites; the central mark of each box indicates the median, and the bottom and top edges indicate the 25th and 75th percentiles. The HGT rates were obtained from comparative genomics data as explained in [44,45]. The gray line in the background is the minimum HGT rate per copy required for parasite persistence (β * ).…”
Section: -P3mentioning
confidence: 99%
See 2 more Smart Citations
“…The evolution of gene content in closely related genomes has been recently investigated by mathematical modeling and comparative genomics 2528 . These analyses have shown that the fraction of genes shared by a pair of genomes decays exponentially with time as the genomes diverge, and that genes can be classified in two categories based on their turnover rates 26 .…”
Section: Resultsmentioning
confidence: 99%